United Education Centre / Bibi Normi Md Noor ... [et al.] - Md Noor, Bibi Normi; Ab. Razak, Ramona; Abd Razak, Norhafizah; Che Mod, Norzalilawaty; Yunus, Nurhuwaina (Faculty of Applied Sciences, 2003)
People have to learn. People learn and keep on learning everyday in every single way to equip themselves with knowledge. In this digital era where information is available at the touch of a button, there's no excuse for learners (term used by United Education Centre to describe students) not to keep up with changes in the studying environment. The name of our business is United Education Centre (UEC), which is another partnership business. After several surveying we finally chose this location because it is very strategic to furnish educational and social aspect for anyone.